2015
DOI: 10.1113/ep085026
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐10 limits intense acute swimming‐induced muscle mechanical hyperalgesia in mice

Abstract: New Findings r What is the central question of this study?This study investigated the role of the endogenous anti-inflammatory cytokine interleukin-10 in intense acute swimming-induced muscle mechanical hyperalgesia in mice. r What is the main finding and its importance?Endogenous interleukin-10 has a key role in limiting exercise-induced muscle pain in a model presenting similarities to delayed-onset muscle soreness in mice. Interleukin-10 reduced muscle pain by diminishing leucocyte recruitment, hyperalgesic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
43
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 58 publications
5
43
1
Order By: Relevance
“…IL-10 deficiency enhances acute exercise-induced muscle hyperalgesia concomitantly with exacerbated oxidative stress [69]. On the other hand, increased nuclear levels of Nrf2 were accompanied by high levels of IL-10 in the plasma and the renal proximal tubules of treadmill-exercised rats [70].…”
Section: •-mentioning
confidence: 93%
“…IL-10 deficiency enhances acute exercise-induced muscle hyperalgesia concomitantly with exacerbated oxidative stress [69]. On the other hand, increased nuclear levels of Nrf2 were accompanied by high levels of IL-10 in the plasma and the renal proximal tubules of treadmill-exercised rats [70].…”
Section: •-mentioning
confidence: 93%
“…Fig 1 shows the time points of treatments and sample collection, which were based on previous studies or selected in experiments shown in the present study [1,2,21]. Mice received vehicle (Vh, 2% DMSO in saline, 200 μg/mL) or quercetin (Qc, 1–30 mg/kg, diluted in 2% DMSO in saline, 200 μg/mL) by intraperitoneal (i.p.)…”
Section: Methodsmentioning
confidence: 99%
“…Mice received vehicle (Vh, 2% DMSO in saline, 200 μg/mL) or quercetin (Qc, 1–30 mg/kg, diluted in 2% DMSO in saline, 200 μg/mL) by intraperitoneal (i.p.) route 30 min before swimming session plus reinforcements 12 h after, depending on the sample collection time point and were submitted to one session of intense acute swimming of 120 min [1,2,21]. The doses of 1, 3 and 10 mg/kg of quercetin were used only in the dose-response experiment presented in Fig 2.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations